Characterization of temporal coherence of hard X-ray free-electron laser pulses with single-shot interferograms. (2017) - Osaka, Taito; Hirano, Takashi; Morioka, Yuki; Sano, Yasuhisa; Inubushi, Yuichi; Togashi, Tadashi
No abstract available